2019
DOI: 10.1136/bmj.l5646
|View full text |Cite
|
Sign up to set email alerts
|

Support for breastfeeding is an environmental imperative

Abstract: Formula milk contributes to environmental degradation and climate change

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 10 publications
1
33
0
1
Order By: Relevance
“…Using the U.S. Environmental Protection Agency Greenhouse Gas equivalencies calculator, it was estimated that this was equivalent to annual GHG emissions from 6.9 billion miles driven in a car. They concluded that formula is “emerging as an important source” of emissions and “relevant to on-going global efforts to address climate change and reduce carbon emissions.” 35 A recent U.K. report, which used the Karlsson et al 52 data for the U.K. estimated that “breastfeeding for 6 months saves an estimated 95–153 kg CO 2 equivalent per baby….equating to taking 50,000 to 77,500 cars off the road each year.” 37 For North America, powdered baby formula Co 2 eq. GHG equates to taking 212,812 cars off the road each year.…”
Section: Discussionmentioning
confidence: 99%
“…Using the U.S. Environmental Protection Agency Greenhouse Gas equivalencies calculator, it was estimated that this was equivalent to annual GHG emissions from 6.9 billion miles driven in a car. They concluded that formula is “emerging as an important source” of emissions and “relevant to on-going global efforts to address climate change and reduce carbon emissions.” 35 A recent U.K. report, which used the Karlsson et al 52 data for the U.K. estimated that “breastfeeding for 6 months saves an estimated 95–153 kg CO 2 equivalent per baby….equating to taking 50,000 to 77,500 cars off the road each year.” 37 For North America, powdered baby formula Co 2 eq. GHG equates to taking 212,812 cars off the road each year.…”
Section: Discussionmentioning
confidence: 99%
“…This makes breastfeeding widely available and environmentally safe. Therefore, breastfeeding’s contribution to sustainability and food security should be considered in environmental goals and policies [230,231].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…While the relationship between breastfeeding and bonding remains an open research question [4], evidence suggests that breastfeeding can help solidify an emotional bond between mothers and infants [5,6]. Beyond the benefits to the mother-child dyad, there are economic and environmental advantages [7,8] to breastfeeding due to the cost of formula, inaccessibility of clean water [9][10][11], and the contribution to plastic waste by formula containers [12]. However, due to a host of personal, cultural, biomedical, socioeconomic and policy factors [13][14][15][16][17][18][19][20], breastfeeding is far from being a behavior which comes easy to mothers [21][22][23][24] or innate to the child [25].…”
Section: Introductionmentioning
confidence: 99%